Pengaruh Metode Index Card Match Terhadap Hasil Belajar Bahasa Indonesia Kelas V MI NW Tanak Mira - Khadijah; Wawan Mulyadi Purnama; Muh. Bisyrulhafy (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to determine the effect of applying the Index Card Match method on Indonesian language learning outcomes regarding the topic of facts and opinions among fifth-grade students at MI NW Tanak Mira for the 2026/2027 academic year. This research employs a quantitative approach using a One-Group Pretest-Posttest Design. The subjects consisted of 14 students. Data were collected through written tests and analyzed using descriptive statistics and hypothesis testing with IBM SPSS Statistics. The results show that the average pretest score of 62.57 increased to 82.29 in the posttest. The ANOVA test yielded a significance value of 0.013 < 0.05, indicating a significant effect. It can be concluded that the Index Card Match method has a positive